Emotions from a Bilingual Point of View : Personality and Emotional Intelligence in Relation to Perception and Expression of Emotions in the L1 and L2. - Ozanska-Ponikwia, Katarzyna (Cambridge Scholars Publishing, 2013)
This book explores the relationship between immersion in a foreign language and its culture, and perception and expression of emotions in both the first and a foreign language. It looks at the perception and expression of emotions from different angles, including personality traits and emotional intelligence as important variables that might have an influence not only on one's ability to perceive and express emotions in a foreign language, but also on self-perceived L2 proficiency in that lan ...